CONSTRUCTION AND ANALYSIS METHODOLOGY OF COMPLEX TECHNICAL INFORMATION SECURITY WITH PROBABILISTIC RELIABILITY AND COUNTING OF TEMPORAL BREAKING ATTEMPTS - Журиленко, Борис Евгеньевич (Ukrainian Information Security Research Journal, 2015)
In this work the theoretical substantiation of single design(SDM) and complex technical information security(CTIS) methodology, based on quantitative assessmentsof the security quality, are made. The methodology isbased on such generalized physical parameters as financialcosts for organization, bulding and modernization technicalinformation security complex, efficiency built protection,the number of hacking attempts and the time atwhich these occurred hacking attempt. On the basis ofthese parameters proposed technical information securitycomplex methodology with quantitative assessment in theform of probabilistic reliability data protection quality. Asa result was received expression of the probability distributionof maximum hacking probability and of attemptsand the time of the hacking attempt, the proposed determiningthe coefficient method efficiency and SDM andCTIS. The influence of effective protection on the probabilityhacking SDM and CTIS, shown how to be a limitingfactor effective protection system to be broken atinfinity or was broken to the desired time of attempts andhacking attempt. Been determined how hacking directioncan influence the real process hacking CTIS. Establishedthat the actual hacking process with the selected conditionscan be projected along the line intersection of twosurfaces - the maximum probability hacking and probability,determined actual hacking attempt. Break point determinedby the intersection direction lines hacking andthe intersection of two surfaces.